Phytogenic Compounds Supplemented to Gestating Hyperprolific Sows Affects the Gut Health-Related Gene Expression and Histological Responses in Neonate Piglets - Reyes-Camacho, David; Pérez, José Francisco; Vinyeta, Ester; Aumiller, Tobias; Criado-Mesas, Lourdes; Folch, Josep Maria; Van der Klis, Jan Dirk; Solà-Oriol, David (Frontiers in Veterinary Science, 2021)
This research aims to determine whether a specific blend of phytogenic compounds (BPC) supplemented in gestating hyperprolific sow diets can promote prenatal maternal effects in terms of piglet gut function and morphology. Twenty-eight (Landrace x Yorkshire) gilts and sows (parity 0 to 7) were randomly distributed by parity number and body weight into two dietary treatments: unsupplemented Control (CON) (n = 14) or CON diet supplemented with 1 g/kg feed of BPC during gestation (n = 14). The BPC supplementation during gestation of sows upregulated the newborn piglets’ jejunal gene expression of SOD2, SLC16A1, SLC11A2, SLC39A, ALPI, and DAO1, while IFN-γ, IDO1 and CLDN4 were downregulated (P < 0.10). In addition, the jejunal villus height and the ratio of the villus height to crypt depth tended to increase (P < 0.10), while goblet cell volume density was higher (P < 0.05) in BPC compared to CON. In conclusion, dietary supplementation of BPC in gestating diets for hyperprolific sows influences neonatal histomorphology and expression of genes related to the intestinal function and health.